Self-reported experiences of siblings of children with life-threatening conditions: A scoping review. (December 2022) - Tay, Joanne; Widger, Kimberley; Stremler, Robyn
Sibling relationships are one of the most long-lasting and influential relationships in a human's life. Living with a child who has a life-threatening condition changes healthy siblings' experience. This scoping review summarized and mapped research examining healthy siblings' experience of living with a child with a life-threatening condition to identify knowledge gaps and provide direction for future research. Studies were identified through five electronic databases. Of the 34 included studies, 17 used qualitative methods, four gathered data longitudinally and 24 focused on children with cancer. Four broad themes of sibling experience were identified across studies: family functioning, psychological well-being, social well-being, and coping. Siblings experienced challenges and difficulties over the course of the child's illness. Future research should incorporate longitudinal designs to better understand the trajectory of siblings' experiences and focus on a wider variety of life-threatening conditions.